Taxonomic Reassessment of Miliusa caudata and Description of a new Miliusa species (Miliuseae—Malmeoideae—Annonaceae) from Andaman and Nicobar Islands, India - Bera, Sukdeb; Karthigeyan, K. (Phytotaxa, 2026)
Miliusa caudata was originally described from the Andaman & Nicobar Islands based solely on fruiting specimens, with floral characteristics remaining unknown. Recent field explorations at the type locality, South Andaman, led to the collection of flowering materials, facilitating the first detailed description of the species’ floral morphology. The observed morphological features, such as sepaloid outer petals, enlarged inner petals, miliusoid stamens, and a densely hairy, sub-globose torus, confirm its generic placement in the genus Miliusa. In addition, a new species, Miliusa saddlepeakensis Sukd.Bera & Karthig. sp. nov., is described and illustrated from the North Andaman. Although the new species bears resemblance to M. andamanica, it can be readily distinguished by its smaller leaves, longer pedicels, larger flowers, and monocarps exhibiting one to two horizontal constrictions when dried.